Gonzo Journalism in the Work of Hunter S. Thompson - Formánek, František (Univerzita Pardubice, 2012)
This paper discusses Gonzo journalism and its characteristics in the work of Hunter S. Thompson. The genre's main features are described in the theoretical part of this paper, and then exemplified in Thompson's seminal novel Fear and Loathing in Las Vegas. The paper also concentrates on the novel's underlying theme; the search for the American Dream. This term is briefly described in the theoretical part and then contrasted with Thompson's opinion about such phenomenon.
Gongo žurnalismus v díle Hunter S. Thompsona
Keywords: Thompson, Hunter S.; Gonzo žurnalismus; Nový žurnalismus; 60. léta ve Spojených státech amerických; Americký sen; Gonzo journalism; New journalism; 1960 in the USA; American Dream